Análise e modelagem de um sistema ambiental sob a influência de ruído de tráfego rodoviário - Robson Caldeira Cruz (2015)
In recent decades, the identification of the main environmental stressors have been the subject of several studies due to a growing concern about the impact of its effects on health and population’s quality of life in general. The existence of high levels of noise in the environment, in which the population lives, works or spends a significant period of the day is a major risk factor the public health issues. In urban environments, noise pollution is caused mainly by road traffic and computational modeling to characterise various indicators of noise pollution in areas of influence of emission sources, whether past, present or future scenarios. This research aimed to model an acoustic environment whose main influence is the noise of motor vehicle traffic, and for that, we used a mapping and sound propagation software in order to diagnose the surroundings of the future Bridge Itaparica Island – Salvador and predict the possible impacts of this project in 2017, which is the year prescribed for the inauguration of the bridge and in 2047, project consolidation year. The results indicated that the current environmental noise Itaparica Island varies according to the distance receivers to road traffic routes, and that over the life of the project, from 2017 to 2047, there will be a continued increase in traffic volume in several stretches. From the Salvador, the forecasts do not indicate significant changes in noise levels, due to it is a densely urbanized area and that, as currently, is characterized by high volumes of traffic . It is hoped that this study will contribute to decision-making in the context of urban planning, with regard to mitigation or attenuation of the problem where it is most needed.